Change impact analysis with a software traceability approach to support software maintenance - Shahid, M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Change impact is an important issue in software maintenance phase. As retesting is required over a software change, there is a need to keep track of software impact associated with changes. Even a small software change can ripple through to cause a large unintended impact elsewhere in the system that makes it difficult to identify the affected functionalities. The impact after changes demands for a special traceability approach. This paper presents a new approach and prototype tool, Hybrid Coverage Analysis Tool (HYCAT), as a proof of concept to support the software manager or maintainers to manage impact analysis and its related traceability before and after a change in any software artifact. The proposed approach was then evaluated using a case study, On-Board Automobile (OBA), and experimentation. The traceability output before and after changes were produced and analyzed to capture impact analysis. The results of the evaluation show that the proposed approach has achieved some promising output and remarkable understanding as compared to existing approaches.